2018
DOI: 10.1039/c8nr07825d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale LuFeO3: shape dependent ortho/hexa-phase constitution and nanogenerator application

Abstract: Ferroelectric and nanogenerator response of ortho and hexa-mixed phase LuFeO3 nanoparticles and nanofibers embedded in a PDMS matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…It is reported that, while the oxidation states do not change, the spectra are sensitive to the changes in the local environments of the Fe 3+ and Lu 3+ sites in the h-and o-structures. We have also recently reported strain-stabilization of different proportions of -o and -h phases in LuFeO3 nanoparticle and nanofiber systems 7 and its consequences for extraordinary polarization and nanogenerator properties. In this work we examine the consequences of the co-existence of o-LFO and h-LFO phases in different proportions in two different nanoscale morphologies i.e.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…It is reported that, while the oxidation states do not change, the spectra are sensitive to the changes in the local environments of the Fe 3+ and Lu 3+ sites in the h-and o-structures. We have also recently reported strain-stabilization of different proportions of -o and -h phases in LuFeO3 nanoparticle and nanofiber systems 7 and its consequences for extraordinary polarization and nanogenerator properties. In this work we examine the consequences of the co-existence of o-LFO and h-LFO phases in different proportions in two different nanoscale morphologies i.e.…”
Section: Introductionmentioning
confidence: 93%
“…We also observed that while going from NP to NF, the Pbnm phase undergoes an increase in strain while the P63cm unit cell slightly relaxes. 7 This shows that the growth model for individual cases of NPs and NFs is quite different from that of the thin film growth model. 5 Based on the observed angles between the (112) planes of the hexagonal and orthorhombic phases in the TEM images, the two phases are seen to be interfaced at φ such that 90°< φ<120°.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations